Integrated Devices for Non‐Invasive Diagnostics. (4th January 2021) - Ates, Hatice Ceren; Brunauer, Anna; von Stetten, Felix; Urban, Gerald A.; Güder, Firat; Merkoçi, Arben; Früh, Susanna Maria; Dincer, Can
Abstract: "Sample‐in‐answer‐out" type integrated diagnostic devices have been widely recognized as the ultimate solution to simplify testing across healthcare systems. Such systems are equipped with advanced fluidic, mechanical, chemical, biological, and electronic components to handle patient samples without any manual steps therefore have the potential to accelerate intervention and improve patient outcomes. In this regard, the combination of integrated devices and non‐invasive sampling has gained a substantial interest to further improve the comfort and safety of patients. In this Review, the pioneering developments in integrated diagnostics are covered and their potential in non‐invasive sampling is discussed. The key properties of possible sample types are highlighted by addressing their relevance for the clinical practice. Last, the factors affecting the transition of integrated devices from academia to the market are identified by analyzing the technology readiness levels of selected examples and alternative remedies are explored to increase the rate of survival during this transition. Abstract : Integrated diagnostic devices are sensor platforms that combine different components for sample handling, recognition elements, signal transduction, processing, transmission units, power suppliers, and decision‐making units to convert physiological information into a desired clinical evaluation within a self‐confined environment. Here, the potential of non‐invasive sampling for integrated diagnostic devices is examined by exploring their compatibilities with "sample‐to‐answer" methods.